The legal nature of taking actions in the property interests of another person without his authorization - Pitsyk K. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to analyze the legal nature, concepts, types and features of the legal regulation of actions in the property interests of another person without his authorization as a non-contractual obligation in the system of civil legal relations. Methodology. The methodology includes a comprehensive analysis and a synthesis of available scientific and theoretical information. It is includes the formulation of relevant conclusions and recommendations. Such methods of scientific knowledge were used: terminological, functional, systemic-structural, logical-normative. Results: In the research process, it was recognized that a person who commits actions for the benefit of another person’s property without his consent is a non-contractual obligation arising on the basis of legal and/or actual actions committed by a person in conditions where there is a risk of negative property consequences and it is impossible obtain the consent of the interested party, including an obligation to reimburse that person for expenses incurred. The parties to the obligation in question are the person who performs actions for the benefit of someone else’s property, the gestor, and the person for whose benefit these actions are performed, the dominus. The gestor and the dominus can be natural or legal entities. The content of the obligations to perform actions in the property interests of another person without his authorization includes the rights and obligations of the manager and the dominus. Scientific novelty. In the process of research, it was established that although the manager acts voluntarily and his activity is not based on a contract or law, he must follow certain rules, in particular, notify the dominus about taking actions in his interests at the first opportunity. These obligations may be the subject of legal proceedings, they are limited to the property interests of the interested person and provide for the prevention, elimination or mitigation of negative property consequences. Practical significance. The results of the research can be used in legislation and law-enforcement activities.